2019
DOI: 10.1073/pnas.1908677116
|View full text |Cite
|
Sign up to set email alerts
|

The MATH-BTB BPM3 and BPM5 subunits of Cullin3-RING E3 ubiquitin ligases target PP2CA and other clade A PP2Cs for degradation

Abstract: Early abscisic acid signaling involves degradation of clade A protein phosphatases type 2C (PP2Cs) as a complementary mechanism to PYR/PYL/RCAR-mediated inhibition of PP2C activity. At later steps, ABA induces up-regulation of PP2C transcripts and protein levels as a negative feedback mechanism. Therefore, resetting of ABA signaling also requires PP2C degradation to avoid excessive ABA-induced accumulation of PP2Cs. It has been demonstrated that ABA induces the degradation of existing ABI1 and PP2CA through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 53 publications
(87 reference statements)
2
66
0
2
Order By: Relevance
“…Alternatively, BPMs may activate additional pathways that counteract some of the MYC-dependent effects. Indeed, previous studies have identified other CUL3 BPM targets such as AtHB6 and PP2CA, a negative regulator of ABA signaling, and several ERF/ AP2 TFs involved in fatty acid metabolism (43,45,70). Consistent with these reports, GO terms related to ABA physiology, such as ABA, water deficit, and water transport, are overrepresented in our transcriptomic analyses.…”
Section: Discussionsupporting
confidence: 89%
“…Alternatively, BPMs may activate additional pathways that counteract some of the MYC-dependent effects. Indeed, previous studies have identified other CUL3 BPM targets such as AtHB6 and PP2CA, a negative regulator of ABA signaling, and several ERF/ AP2 TFs involved in fatty acid metabolism (43,45,70). Consistent with these reports, GO terms related to ABA physiology, such as ABA, water deficit, and water transport, are overrepresented in our transcriptomic analyses.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our data also suggest that COP1 might not be the only E3 ligase involved in the degradation of clade A PP2Cs, since the ABI1 and AHG3 levels still decreased in the cop1‐4 mutant after ABA treatment. Our results are consistent with previous reports indicating that other E3 ligases, such as PUB12/13, RGLG1/5, and BPM3/5, are also involved in the regulation of the stability of PP2Cs (Kong et al ., 2015; Wu et al ., 2016; Julian et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, under stressed conditions or ABA treatment, activities of PP2Cs can be reduced by ABA receptor PYLs and several other regulators, such as the putative leucine‐rich repeat‐RLK, RECEPTOR DEAD KINASE1 (RDK1) that can promote ABA responses by interacting with ABI1 (Kumar et al 2017). PP2Cs are also degraded by the 26S proteasome pathway through the PUB12/13 U‐box, RGLG1/5 RING‐type and multimeric cullinc3 (CUL3)‐RING‐based E3 ligases by interacting with the adaptor BTB/POZ AND MATH DOMAIN proteins (BPMs), which is promoted by ABA (Figure 2) (Kong et al 2015; Wu et al 2016; Belda‐Palazon et al 2019; Julian et al 2019).…”
Section: Core Aba Signalingmentioning
confidence: 99%